A Berriasian actinopterygian fauna from Cherves-de-Cognac, France: Biodiversity and palaeoenvironmental implications. (July 2015) - Pouech, Joane; Mazin, Jean-Michel; Cavin, Lionel; Poyato-Ariza, Francisco J.
Abstract: The paleontological site of Cherves-de-Cognac (Charente, southwestern France) is an 81-levels sedimentary series, which records deposits from a coastal lagoon to a continental lake, reflecting the general regressive context of the Upper Jurassic-Lower Cretaceous. This site has yielded a rich and diversified vertebrate fauna from the Lower Cretaceous, including numerous actinopterygian remains described here. Cranial bones and scales have been found as macro-remains during excavations, and are all referable to the ginglymodian Scheenstia mantelli . In parallel, an important program for extracting and sorting vertebrate dental micro-remains from the 63 fossiliferous levels of the series, has led to a collection of more than 26, 000 actinopterygian isolated teeth. Among these specimens, eleven tooth morphotypes can be distinguished. Tooth morphotypes 1 and 2 are the more commonly found and are identified as respectively "oral" and "pharyngeal" teeth of S. mantelli . Tooth morphotypes 3 to 5 are less frequent and referred to Caturus sp., Belonostomus sp. and Thrissops sp. respectively. Tooth morphotypes 6 to 11 correspond to Pycnodontiformes morphologies, morphotype 6 being the most represented in the sedimentary series after morphotype 1. Review of known ecologies of these taxa, together with palaeoenvironmental data available for the site of Cherves-de-Cognac, indicate a fresh to brackish life environment for S. mantelli and Pycnodontiformes. Graphical abstract: Highlights: Actinopterygian remains from a French Berriasian site have been studied. Cranial bones are referred to the ginglymodian Scheenstia mantelli. 11 morphotypes have been recognized among 26, 000 isolated teeth. Quantitative data allow avoiding taxonomic ambiguity. A fresh-to brackish habitat is proposed for S. mantelli and Pycnodontiformes.